Insights into Food Buying Decision: - Stoica, Dimitrie; Bichescu, Cezar I.; Stoica, Maricica (The Journal of Accounting and Management, 2024)
This study aims to explore the stages of consumer purchasing decisions for food products, with a particular focus on the influences of price, emotion, packaging, and labeling. The process of consumer purchasing involves several key stages, such as recognition an unsatisfied need, seeking information, evaluating alternatives, making the purchase, and conducting a post-purchase evaluation. Among these, the stages of information search and mental evaluation are particularly critical, as consumers utilize various sources to assess products, particularly in relation to price, packaging, and labeling. Price plays a significant role in influencing emotions and purchasing intentions, with positive perceptions promoting purchases and negative ones discouraging them. Packaging significantly affects the decision-making, especially for low-involvement purchases, as it can evoke strong emotional responses through elements such as colors and images. Food labels serve as essential communication tools, shaping consumer perceptions and decisions; health and hedonistic labels, in particular, can influence skepticism and evaluation processes. Effective marketing strategies that address both the cognitive and emotional dimensions of consumer behavior can enhance decision-making processes, reduce post-purchase dissonance, and foster long-term satisfaction and loyalty.